2022
DOI: 10.3390/app12031331
|View full text |Cite
|
Sign up to set email alerts
|

A Task Allocation Strategy of the UAV Swarm Based on Multi-Discrete Wolf Pack Algorithm

Abstract: With the continuous development of artificial intelligence, swarm control and other technologies, the application of Unmanned Aerial Vehicles (UAVs) in the battlefield is more and more extensive, and the UAV swarm is increasingly playing a prominent role in the future of warfare. How tasks are assigned in the dynamic and complex battlefield environment is very important. This paper proposes a task assignment model and its objective function based on dynamic information convergence. In order to resolve this mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Experiments have shown that the algorithm is more accurate and converges faster [7]. Literature proposed the cultural wolf optimization algorithm, and found that the cultural wolf optimization algorithm has faster convergence speed and higher accuracy than other algorithms in the actual use process [8]. Literature adds new random survival rules on the basis of WPA, and ensures the diversity of algorithms by adding new rules [9].…”
Section: Related Workmentioning
confidence: 99%
“…Experiments have shown that the algorithm is more accurate and converges faster [7]. Literature proposed the cultural wolf optimization algorithm, and found that the cultural wolf optimization algorithm has faster convergence speed and higher accuracy than other algorithms in the actual use process [8]. Literature adds new random survival rules on the basis of WPA, and ensures the diversity of algorithms by adding new rules [9].…”
Section: Related Workmentioning
confidence: 99%
“…The fish swarm algorithm incorporates four behaviors: foraging, aggregation, tail chasing, and random [32], while the wolf pack algorithm includes three behaviors: wandering, summoning, and siege [33]. Despite differences, there are similarities between these behaviors.…”
Section: Solving Based On Wf-csa Optimization Algorithmmentioning
confidence: 99%
“…Substitute x i into (33),and reorder according to the fitness value from small to large, to get the position of the leader fish, scout fish, and hunter fish x a , x b , x c Substitute x a into (33) to get best f itness 21: end while…”
mentioning
confidence: 99%
“…The adjustment of impact degree. In the initial stage of dispersion, if the judgment of influence degree cannot guarantee the comprehensiveness, the overall performance of the judgment result of influence degree will be reduced Xu et al [ 11 ]. Therefore, in the process of influencing factor analysis, we should try our best to expand the judgment range, narrow the judgment range near the main influencing factors of habit formation, and constantly adjust the factors to improve the success rate of habit formation.…”
Section: Concepts Related To the Continuous Discrete Algorithmmentioning
confidence: 99%